Representation matters a comparative analysis of the media coverage of Inquirer.net and Philstar.com on the UAAP Season 86 collegiate sports. - Santos, Arriana T.
This research examines the media coverage of Inquirer.net and Philstar.com during the UAAP Season 86 focusing on the extent, nature, and patterns in reportage. A textual analysis of all published articles by both news outlets throughout the season was done to determine coverage patterns and dominant themes. Interviews with editors and journalists provided further insights into the decision-making process occurring in the newsrooms. Findings were then analyzed utilizing Shoemaker’s (1985) concept of news values. Results revealed that there is a significant disparity in reporting across sports, with both outlets heavily focused on men's basketball and women's volleyball while other sports received minimal coverage or none. Emphasizing proximity, prominence, and timeliness as key determinants in sports reporting, most articles were written because basketball and volleyball are culturally ingrained, widely relatable, and deeply embedded in the culture of the country. The prominence of both sports ensures significant media coverage as they align with the audience’s interests. However, there is still a gap between coverage in the men’s and women’s division of both sports wherein men’s volleyball and women’s basketball receive minimal coverage compared to their counterparts. The lack of coverage on other sports aside from basketball and volleyball affirms the need for a more inclusive sports reporting that extends coverage for a more equitable sports media landscape.